Sediment echosounder processed data (Atlas Parasound P70 echosounder working area dataset) of RV Maria S. Merian during cruise MSM105, Namibian Shelf, South Atlantic Ocean - Nikolas Römer-Stange (PANGAEA, 2024)
Digital sediment echo sounder profiles were acquired along five transects across the Namibian Shelf in the southeast Atlantic ocean with the hull mounted Atlas Parasound P70 onboard RV Maria S. Merian during the research expedition MSM105 (11.01.-23.02.2022). A continuous wave with a rectangular shape and a pulse length of 50 μs has been transmitted, resulting in decimetric scale vertical resolution and a maximum penetration of 60-70 m. For geologic interpretation and further analysis of the cores on the transect at 23°S, this profile has been further processed and converted to depth. A total of five horizons are interpreted.